2012
DOI: 10.5539/jas.v4n12p155
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Grain Yield of Pearl Millet (Pennisetum glaucum) Genotypes at Different Levels of Nitrogen Fertilization in the Southeastern United States

Abstract: Pearl millet (Pennisetum glaucum [L.] R. Br) has the requisite characteristics for dry land production in the southeastern USA in comparison to the traditional grain crops while requiring less input. The purpose of this study was to identify the genotypes that produce the highest yield and seed quality at different rates of nitrogen. Four pearl millet genotypes (2304, LHB08, 606A1*2304 and 707A1*4280) were cultivated on secondary land and treated with 4 different nitrogen rates: 0, 40, 80 and 120 kg ha -1 . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
7
12
1
Order By: Relevance
“…Furthermore, a negative relation was detected, in the current study, between number of tillers and plant height, the taller the plants, the less the number of produced tillers. This observation was consistent with the findings of Obeng et al (2012).…”
Section: Cultivar X Fertilizer Interactionsupporting
confidence: 83%
“…Furthermore, a negative relation was detected, in the current study, between number of tillers and plant height, the taller the plants, the less the number of produced tillers. This observation was consistent with the findings of Obeng et al (2012).…”
Section: Cultivar X Fertilizer Interactionsupporting
confidence: 83%
“…Pearl millet has been reported to produce substantial yield on marginal land and with minimal N input (Obeng et al 2012). This study shows that higher N rates may result in enhanced insect infestation impacting the yield.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional cereal crops, pearl millet requires lower amounts of resources for its growth and can grow in adverse conditions (e.g., water and fertilizer shortage) due to its physiological characteristics [24,65]. In one field study, four pearl millet genotypes (2304, LHB08, 606A1*2304, and 707A1*4280) were grown using four different quantities of nitrogen: 0, 40, 80, and 120 kg ha −1 [66]. The results from this study showed that the application of N fertilizer in varying quantities does not have any significant effect on the head length, plant (dry) weight, and the final yield of pearl millet.…”
Section: Milletmentioning
confidence: 99%